1994
DOI: 10.1177/095968369400400209
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive high-resolution record of late Holocene climatic change from a raised bog in northern England

Abstract: Proxy-climatic data in the form of plant macrofossils have been analysed from a 5 m core from Bolton Fell Moss, Cumbria, UK. Detailed analysis of peat from the upper 50 cm of this core is used to demonstrate a strong correlation between changes in the relative proportion of taxa and known climatic changes over the last 1000 years. The record of changes in bog vegetation contained within the peat profile is used to reconstruct changes in bog-surface wetness for the latter half of the Holocene. As bog- surface w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
273
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(279 citation statements)
references
References 11 publications
4
273
0
2
Order By: Relevance
“…In the absence of recent disturbance, the extent of peat decay generally increases with depth such that preferential decay is more commonly invoked to explain surface depletion in N rather than surface enrichment. To a first order, the intensity of peat decay varies with the duration that peat remains within the periodically oxygenated acrotelm (Malmer and Wallén (2004), and thus is expected to show periodic fluctuations in response to changing climate (Barber et al, 1994) and peat drainage (Blackford and Chambers, 1991). It is on this basis that Wang et al (2015) attribute their observed increase in N concentration with depth in the peat to preferential loss of C during peat decomposition.…”
Section: N and P Enrichment In Surface Peatmentioning
confidence: 99%
“…In the absence of recent disturbance, the extent of peat decay generally increases with depth such that preferential decay is more commonly invoked to explain surface depletion in N rather than surface enrichment. To a first order, the intensity of peat decay varies with the duration that peat remains within the periodically oxygenated acrotelm (Malmer and Wallén (2004), and thus is expected to show periodic fluctuations in response to changing climate (Barber et al, 1994) and peat drainage (Blackford and Chambers, 1991). It is on this basis that Wang et al (2015) attribute their observed increase in N concentration with depth in the peat to preferential loss of C during peat decomposition.…”
Section: N and P Enrichment In Surface Peatmentioning
confidence: 99%
“…Ordination techniques (PCA and DCA) have been used to create a single index of mire surface wetness based on the total sub-fossil dataset for a peat profile (Barber et al, 1994;Mauquoy et al, 2004b;Sillasoo et al, 2007), in which it is assumed that the principal axis of variability in the dataset is linked to hydrology. Quantitative reconstructions of local water-table depths are also possible, based on water table/ surface vegetation modelling (Väliranta et al, 2007).…”
Section: Plant Macrofossilsmentioning
confidence: 99%
“…Nevertheless there are problems in using these techniques. For example, in using DCA, Barber et al (1994) had to combine the records of Sphagnum magellanicum with S. imbricatum, because otherwise the first component in the data was the stratigraphic difference between the lower horizons dominated by S. imbricatum, and the upper horizons, dominated by S. magellanicum, which seemed to be its direct replacement. This example cautions researchers to be fully aware of the patterns in the dataset, and not to assume that the first component will automatically be hydrological.…”
Section: Plant Macrofossilsmentioning
confidence: 99%
See 1 more Smart Citation
“…This development also suggests an increase in hydraulic energy through increased precipitation as the climate cooled during the Subboreal, at about 4500 cal. BP ( [Barber et al, 1994], [Johnsen et al, 2001] and [Magny et al, 2006]). In stretch D, where the floodplain is wider, the main channel incision led to the abandoning of some channels, such as the RIA palaeochannel, which can be seen on the conductivity map (Fig.…”
Section: Spatial Variability and Forcing Factors Of The River Morpho-mentioning
confidence: 99%